Contribution of Federal Centre for Animal Health to Rosselkhoznadzor’s international mandate delivery - V. V. Lavrovsky (Ветеринария сегодня)
The paper covers the history of the Federal Centre for Animal Health, which started 65 years ago by the foundation of the All-Union Foot and Mouth Disease Research Institute. The main research area – FMD prevention and control – was and still remains the leading one for the Centre. The current history of the Federal Centre for Animal Health development is inextricably associated with the public administration reform in agriculture in 2000s, when the Federal Service for Veterinary and Phytosanitary Surveillance (Rosselkhoznadzor) spun off the Ministry of Agriculture of the Russian Federation as an independent executive authority with broad powers in the area of the veterinary and phytosanitary control and surveillance. The grounds for the re-subordination of the Federal Centre for Animal Health to the Rosselkhoznadzor, historically novel executive authority in Russia, included high international prestige of the Centre and nationally and internationally acknowledged qualification of its employees in the field of contagious animal diseases.